2019
DOI: 10.1136/bcr-2019-231331
|View full text |Cite
|
Sign up to set email alerts
|

Risk of vasopressin use: a case of acute pulmonary oedema, post intramyometrial infiltration of vasopressin in laparoscopic myomectomy

Abstract: A 34-year-old patient underwent a laparoscopic myomectomy, complicated by a profound episode of bradycardia and hypotension following intramyometrial infiltration of vasopressin (20 IU), promptly corrected with intravenous ephedrine (6 mg) and glycopyrrolate (200 µg). At extubation, pink frothy fluid was noted in the endotracheal tube; she was visibly distressed, desaturated to 89% in air and was coughing up pink stained fluid. Acute pulmonary oedema secondary to vasopressin was suspected. A tight-fitting oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…It is important to note that the evidence for vasopressin as a single agent is limited compared with that of misoprostol and is based on a single RCT of 20 patients conducted in 1994 which showed a reduction in blood loss of 450 ml but no reduction in the need for blood transfusion 32 . The serious side effects of vasopressin (bronchospasm, cardiac arrest, angina and fluid imbalance) 33 which must be balanced against any haemorrhage‐reducing benefit, have resulted in its prohibition for use at myomectomy in some European countries.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the evidence for vasopressin as a single agent is limited compared with that of misoprostol and is based on a single RCT of 20 patients conducted in 1994 which showed a reduction in blood loss of 450 ml but no reduction in the need for blood transfusion 32 . The serious side effects of vasopressin (bronchospasm, cardiac arrest, angina and fluid imbalance) 33 which must be balanced against any haemorrhage‐reducing benefit, have resulted in its prohibition for use at myomectomy in some European countries.…”
Section: Discussionmentioning
confidence: 99%
“…Barcroft et al reported a case of acute pulmonary edema which developed in a case of laparoscopic myomectomy after infiltration of 20 U of vasopressin. 1 This case initially developed bradycardia and hypotension which was managed with glycopyrrolate, ephedrine and crystalloids. The patient settled down but at extubation was found to have pink frothy sputum and desaturated to 89% suggesting that she developed acute pulmonary edema.…”
Section: Discussionmentioning
confidence: 99%
“…Although intra-myometrial vasopressin results in very good surgical hemostasis it may cause adverse cardiac events like bradycardia, arrhythmia, cardiac arrest and pulmonary oedema and lethal catastrophe if not diagnosed and managed soon. [1][2][3][4] We report a case of successful resuscitation following bradycardia and impending cardiac arrest by intra-myometrial injection of vasopressin in a case of laparoscopic myomectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, AVP triggers MAPK-induced endothelial dysfunction with direct effect for release of clotting factors [59] , [60] . Remarkably, administration of AVP reduces development of ALI [61] however, Barcroft et al, illustrated in a case-report study that intramyometrial infiltration of AVP during laparoscopic myomyectomy leads to acute pulmonary edema and coronary vasospasm [62] . Thus, dose-dependent effect of AVP may affect the cardiopulomary outcomes.…”
Section: Arginine Vasopressin and Covid-19mentioning
confidence: 99%